Howard Frank Mosher and the classics echoes in the Vermont writer's works - Saunders, James Robert 1953- (McFarland, 2014)
"This book draws connections between Vermont author Howard Frank Mosher and works of classic American literature. From Chapter I exploring the horrors of the Civil War as conveyed in Mosher's Walking to Gatlinburg and Stephen Crane's The Red Badge of Courage, to Chapter VIII offering romantic love as a shield against other human beings"--